THE FUNCTIONS OF EXPRESSIVE SPEECH ACTS AND THEIR EMOTIONAL DEPICTION IN THE FILM OF DISNEY’S MALEFICENT - Maskuri, Sri Kuncoro Dibyo Sarjono; Syafrianto; Carreon, Jonathan Rante; Istiqomah, Fitria Naimatul (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
This investigation aspires to identify the functions of expressive speech acts performed by the characters in the film of Disney’s Maleficent. Using pragmatic approach the investigation analyzed how these expressive utterance relate to basic emotions. The qualitative descriptive method was used in the recent investigation; dialogues from the film script were collected, grouped into twelve categories of expressive acts, and examined based on six core emotions. The results indicated that eleven functions of expressive speech acts were identified, they were complaint, lamentation, greeting, compliment, apologies, protest, deplore, boast, praise, thanking, and congratulating. The expressive functions were used to highlight the themes of betrayal and conflict in the film. In addition, the expressive functions reflected the basic emotional states of the characters in the film. The basic emotions emerged in the utterances of expressive functions were anger, happiness, sadness, disgusting, fear, and surprise. These findings suggested that expressive actions not only facilitated communication but also reflected emotional states and narrative conflicts. This research enhances the understanding of how films utilize language to depict complex emotions and enrich character development.